Dental education, Teledentistry and the COVID-19 pandemic: a narrative review (Research, Society and Development, 2022)
This study aimed to review and address the possibilities of applying teledentistry in dental education in order to break paradigms and spread this new tool after the COVID-19 pandemic. Methodology: This work is a narrative review of the literature based on document analysis of official guidelines and published articles. Between 2019 and 2022, a systematic search was carried out in the PubMed and Google Scholar databases, with the following descriptors: “Teledentistry” AND “Privacy” AND “Dental Education” AND “Health Technologies” AND “Telehealth” AND “COVID -19”. Results: Telescreening and telemonitoring were the most used and regulated approaches to teledentistry during the pandemic, as they proved to be efficient in continuing the process of remote dental care. They were adopted in several countries such as the Philippines, Italy, Hong Kong, Brazil, the United States, Canada and Jordan, which had their dental teaching activities suspended during the pandemic and opted for online remote teaching. In addition, teacher and student training for remote learning took place on several continents. Conclusion: Teledentistry is a tool to complement the traditional methods of education and performance in dentistry, because it is little recognized and practiced by dental surgeons, it is essential to address the possibilities of application of this modality to new means of performance of the dental class.